Arsenic exposure assessment from ground water sources in Peshawar Basin of Khyber Pakhtunkhwa, Pakistan - Khattak, Seema Anjum; Polya, David; Ali, Liaqat; Shah, Mohammad Tahir (Journal of Himalayan Earth Sciences, 2016)
Arsenic contaminated groundwater in some south Asian countries like Bangladesh and West Bengal India is one of the largest environmental health hazards in the world. PCRWR with the help of UNICEF has carried out a nationwide survey for drinking water arsenic contamination in different parts of Pakistan which also included limited number of samples from Mardan, Peshawar and Mingora in KPK province. In order to know the existence of arsenic contamination in ground water of the Peshawar basin, about 30 drinking exposure (human hair and nails samples from different parts of the Peshawar basin have been collected. Drinking/cooking water, raw rice, hair and nails samples were analyzed for total arsenic by ICP-MS. Chronic Daily Intake (CDI mg/Kg Body weight) was calculated for arsenic risk assessment of all the volunteers who participated in this study. All drinking/cooking water samples were found below the 10 µg/L arsenic concentration which is the WHO provisional guideline values. The results were also confirmed by the biomarkers of arsenic exposure from the study population.